Cheilostome Bryozoa from Penang and Langkawi, Malaysia - Taylor, Paul D.; Tan, Aileen Shau Hwai (Consortium of European Natural History Museums, 2015)
Twenty-three species of cheilostome bryozoans are described from the Malaysian islands of Penang and Langkawi based on a brief reconnaisance survey of shore localities. These are the first bryozoans to be formally described from either island and they demonstrate the potential for further research on these neglected suspension feeders. Of the 23 species recorded, 12 are anascans, half of which are malacostegines, and 11 are ascophorans. The new combinations Acanthodesia falsitenuis (Liu, 1992), A. perambulata (Louis & Menon, 2009) and A. irregulata (Liu, 1992) are introduced. Most of the species recorded are widespread in the Indo-Pacific, and some are apparently globally distributed in the tropics and subtropics, including the invasive fouling species Bugula neritina, Hippoporina indica and Schizoporella japonica, as well as the coral reef associates Cranosina coronata and Hippopodina feegeensis. Plastic debris and glass bottles were encrusted by Jellyella eburnea, a coloniser of floating biological and man-made objects that is becoming widespread in the tropics and subtropics of the world’s oceans.